Ayşe Nur Yamanus, The Ash'arî School of Hadith - Ural, Cemal (Samsun University, 2024)
Shortly after the passing of the Prophet Muhammad, disputes that emerged among Muslims paved the way for the development of diverse perspectives and the formation of various sects around these ideas. These sects influenced both their adherents and opposing groups in different ways. In recent years, the academic study of schools of thought that have left a lasting impact on Islamic intellectual history has become a promising trend in our country. Numerous sects, such as Mu‘tazila, M?tur?d?sm, Ash‘arism, ??hirism, and Ib??ism, have been analyzed from different angles, and research in this field continues. Within this context, Ayşe Nur Yamanus's doctoral dissertation titled The Ash‘ar? Hadith School is a valuable contribution to the literature. This article aims to examine the dissertation.

Hz. Peygamber’in vefatından kısa bir süre sonra Müslümanlar arasında ortaya çıkan ihtilaflar, farklı düşüncelerin gelişmesine ve bu düşünceler etrafında çeşitli mezheplerin oluşmasına zemin hazırlamıştır. Bu mezhepler hem kendi müntesiplerini hem de karşıt mezhepleri çeşitli şekillerde etkilemiştir. Ülkemizde son yıllarda, İslam düşünce tarihinde iz bırakmış ekollerin akademik çalışmalara konu edilmesi sevindirici bir gelişme olarak öne çıkmaktadır. Mutezile, Mâturîdîlik, Eş‘arî’lik, Zâhirîlik ve İbâdîlik gibi pek çok mezhep, farklı yönleriyle incelenmiş ve incelemeler devam etmektedir. Bu kapsamda, Ayşe Nur Yamanus’un Eş‘arî Hadis Ekolü başlıklı doktora tezi de literatüre katkı sağlayan önemli bir çalışmadır. Bu makale, söz konusu tezi incelemeyi hedeflemektedir.
Ayşe Nur Yamanus, Eş‘arî Hadis Ekolü
Keywords: Hadith; Hadis